Efektivitas Konseling REBT Pendekatan Teknik Self-Talk Untuk Menurunkan Tingkat Kecemasan Akademik Siswa Kelas X SMAN “A” Denpasar - Ni Kadek Rista Ary Putri; Ni Ketut Suarni; I Ketut Dharsana (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
This study aims to (1) find out the relationship between the use of the REBT counseling approach  to self-talk techniques to  reduce students' academic anxiety levels, (2) to know the benefits of the importance of self-talk techniques for students, (3) to find out the obstacles faced by students in the teaching and learning process in schools.  The method used in this study was Pretest-Posttest Control Group Design.  The subjects of this study were class X students of SMAN "A" Denpasar. Data collection was carried out using Albert Ellis's academic anxiety scale which consisted of four aspects, namely psychological, motor, cognitive, somatic totaling 35 questions. The data analysis used is Anava One Line. According to the calculation results using the Statistical Packages for Social Science (SPSS) for Windows program version 21.0.  Based on the results of the analysis obtained REBT counseling model self-talk technique is effective for reducing student anxiety levels. The result t = 14.89 at df = 51 with a significance level of 5% was obtained, then the table t value =2.00 was obtained. Based on these results, it can be concluded that the tvalue of calculating  > ttable or 14.89 > 2.00 is classified as having high effectiveness, meaning that there is an influence of REBT counseling self-talk techniques to reduce academic anxiety levels.